2014
DOI: 10.1155/2014/173187
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between an Acrylic Splint Herbst and an Acrylic Splint Miniscrew-Herbst for Mandibular Incisors Proclination Control

Abstract: Aim. The aim of this study is to compare dental and skeletal effects produced by an acrylic splint Herbst with and without skeletal anchorage for correction of dental class II malocclusion. Methods. The test group was formed by 14 patients that were treated with an acrylic splint miniscrew-Herbst; miniscrews were placed between mandibular second premolars and first molars; controls also consisted of 14 subjects that were treated with an acrylic splint Herbst and no miniscrews. Cephalometric measurements before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 20 publications
3
54
0
Order By: Relevance
“…Power and sample size calculation (PS) software (Vanderbilt University, Nashville, Tenn) was used. It was based on the work of Manni et al, 17 who reported a 3.7 6 2.26 mm difference in the mandibular length. When the power was set at 90%, the required sample size was found to be 11 subjects per group.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…Power and sample size calculation (PS) software (Vanderbilt University, Nashville, Tenn) was used. It was based on the work of Manni et al, 17 who reported a 3.7 6 2.26 mm difference in the mandibular length. When the power was set at 90%, the required sample size was found to be 11 subjects per group.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…The use of fixed functional appliances in particular has the advantages of requiring minimal patient compliance and ensuring a constant anterior positioning of the mandible during the treatment period (22,23) . One of the commonly used rigid fixed functional appliances is the Herbst appliance, where several studies have investigated its effects and compared it to the effects of other functional appliances (24)(25)(26)(27) .…”
Section: Introductionmentioning
confidence: 99%
“…The sample size calculation was based on a study by Manni et al 29 who compared the use of Herbst appliance with and without mini screw anchorage and reported a significant increase in the Herbst mini screw group over their control group. The mean change in the mandibular length in the treatment and control groups were 4.6±2.43 mm and 0.9±2.09 mm respectively.…”
Section: Sample Size Calculationmentioning
confidence: 99%